Evaluation of proximal slicing in primary maxillary incisors with proximal caries- a retrospective cohort study - Avia Fux-Noy; Tamar Goldberg; Aviv Shmueli; Elinor Halperson; Diana Ram; Esti Davidovich; Moti Moskovitz (BMC, 2023)
Abstract Background Modern management of dental caries should be more conservative and include early detection of lesions and active surveillance, in order to apply preventive measures and carefully monitor for signs of arrest or progression. Proximal slicing was suggested for nonrestorative caries treatment for primary incisors. The aim of the study was to examine the success of proximal slicing in primary maxillary incisors in arresting caries progression. Methods A retrospective cohort study. Data were collected from medical records of patients who had undergone proximal slicing in primary maxillary incisors with a follow-up period of at least 6 months. Treatment was considered a success when no further invasive clinical intervention was required within the follow-up period of at least 6 months. Treatment was considered a failure when further invasive clinical intervention was needed during the follow-up period (restoration, crown, or extraction). Additional variables included were the patient's gender, treated tooth, treated surface, age during their first visit to the clinic, age during slicing treatment, follow-up period, number of follow-up visits, and number of fluoride applications and additional slicing during follow-up. Results Seventy-one patients were included in the study. Proximal slicing was successful in 76% of participants with a follow-up of at least 6 months. Success was associated with older age at the first dental visit (3.5yo vs. 2.5yo, p = 0.0011) and age when proximal slicing was performed (4yo vs. 3yo, p < 0.001). Conclusion Proximal slicing may successfully arrest proximal caries in primary maxillary incisors.